Mobile and Wireless Communications Networks IFIP TC6 / WG6.8 Conference on Mobile and Wireless Communication Networks (MWCN 2004) October 25-27, 2004 Paris, France - Belding-Royer, Elizabeth M.; Al Agha, Khaldoun; Pujolle, Guy.; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2005)
Mobile Ad hoc NETworks (MANETs) has attracted great research interest in recent years. A Mobile Ad Hoc Network is a self-organizing multi-hop wireless network where all hosts (often called nodes) participate in the routing and data forwarding process. The dependence on nodes to relay data packets for others makes mobile ad hoc networks extremely susceptible to various malicious and selfish behaviors. This point is largely overlooked during the early stage of MANET research. Many works simply assume nodes are inherently cooperative and benign. However, experiences from the wired world manifest that the reverse is usually true; and many works [3] [10] [9] [8] [12] [19] have pointed out that the impact of malicious and selfish users must be carefully investigated. The goal of this research is to address the cooperation problem and related security issues in wireless ad hoc networks. As a rule of thumb, it is more desirable to include security mechanisms in the design phase rather than continually patching the system for security breaches. As pointed out in [2] [1], there can be both selfish and malicious nodes in a mobile ad hoc network. Selfish nodes are most concerned about their energy consumption and intentionally drop packets to save power. The purpose of malicious nodes, on the other hand, is to attack the network using various intrusive techniques. In general, nodes in an ad hoc network can exhibit Byzantine behaviors.
Understanding the Interactions between Unicast and Group Communications Sessions in Ad Hoc Networks -- Cross-Layer Simulation and Optimization for Mobile Ad-Hoc Networks -- Improving TCP Performance over Wireless Networks Using Loss Differentiation Algorithms -- TCP Performances in a Hybrid Broadcast/Telecommunication System -- Handoff Notification in Wireless Hybrid Networks -- Selective Active Scanning for Fast Handoff in WLAN using Sensor Networks -- An Analysis of Mobile IPv6 Signaling Load in Next Generation Mobile Networks -- Peer-to-Peer Based Architecture for Mobility Management in Wireless Networks -- Supporting Groupware in Mobile Networks -- RSM-WISP: Roaming and Service Management in Hotspot Networks Through a Policy Based Management Architecture -- Integrated Reconfiguration Management for the Support of End to End Reconfiguration -- Replica Allocation Considering Data Update Intervals in Ad Hoc Networks -- Anova-Informed Decision Trees for Voice Applications over Manets -- Route Stability Techniques for Enhanced Video Delivery on Manets -- A New Smoothing Jitter Algorithm for Voice over Ad Hoc Networks -- On the Complexity of Radio Resources Allocation in WCDMA Systems -- Optimization of Pilot Power for Service Coverage and Smooth Handover in WCDMA Networks -- An Alternative Metric for Channel Estimation with Applications in Bluetooth Scheduling -- Distributed Pairwise Key Generation Using Shared Polynomials for Wireless Ad Hoc Networks -- Collaboration Enforcement and Adaptive Data Redirection in Mobile Ad Hoc Networks Using Only First-Hand Experience -- A Simple Privacy Extension for Mobile IPv6 -- A Trust-Based Routing Protocol for Ad Hoc Networks -- Short-Term Fairness of 802.11 Networks with Several Hosts -- RAAR: A Relay-Based Adaptive Auto Rate Protocol for Multi-Rate and Multi-Range Infrastructure Wireless LANs -- A Non-Token-Based-Distributed Mutual Exclusion Algorithm for Single-Hop Mobile Ad Hoc Networks -- The Receiver’s Dilemma -- Theoretical Capacity of Multi-Hop Wireless Ad Hoc Networks -- How to Discover Optimal Routes in Wireless Multihop Networks -- Asymptotic Pheromone Behavior in Swarm Intelligent MANETs -- Randomized Routing Algorithms in Mobile Ad Hoc Networks -- RBR: Refinement-Based Route Maintenance Protocol in Wireless Ad Hoc Networks -- Enabling Energy Demand Response with Vehicular Mesh Networks -- Context-Aware Inter-Networking for Wireless Networks -- Performance Impact of Mobility in an Emulated IP-based Multihop Radio Access Network -- Broadcast Services and Topology Control in Ad-Hoc Networks -- Space and Time Curvature in Information Propagation in Massively Dense Ad Hoc Networks -- Cluster-based Location-Services for Scalable Ad Hoc Network Routing -- On Selecting Nodes to Improve Estimated Positions -- Energy-Efficient Multimedia Communications in Lossy Multi-hop Wireless Networks -- Analyzing the Energy Consumption of IEEE 802.11 Ad Hoc Networks -- Energy-Efficient Reliable Paths for On-Demand Routing Protocols -- Minimum Power Symmetric Connectivity Problem in Wireless Networks: A New Approach.
Keywords: Electrical engineering; Computer organization; Computer communication systems; Communications Engineering, Networks; Computer Systems Organization and Communication Networks; Computer Communication Networks